Extracellular Calcium Dictates Onset, Severity, and Recovery of Diarrhea in a Child with Immune-Mediated Enteropathy - Fraebel, Johnathan; Gonzalez-Peralta, Regino; Maximos, Maryann; Beasley, Genie L.; Jolley, Christopher Douglas; Cheng, Sam Xianjun (Frontiers in Pediatrics, 2018)
Diarrhea causes monovalent and divalent ion losses that can influence clinical outcome. Unlike the losses of monovalent ions, such as Na+, K+, Cl- and HCO3-, which are generally large in quantity (osmoles), and therefore determine the severity of diarrhea, the losses of divalent ions are relatively small in osmoles and are often overlooked during diarrheal treatment. Studies now suggest that despite divalent ions being small in osmoles their effects are large due to the presence of divalent ion-sensing receptors and their amplifying effects in the gut. As a result, losses of these divalent ions without prompt replacement could also significantly affect the onset, severity and/or recovery of diarrheal disease. Herein, we report a case of a malnourished child with an immune-mediated enteropathy who developed episodes of “breakthrough” diarrhea with concurrent hypocalcemia while on appropriate immunotherapy. Interestingly, during these periods of diarrhea, stool volume fluctuated with levels of blood Ca2+. When Ca2+ was low, diarrhea occurred; when Ca2+ levels normalized with replacement, diarrhea stopped. Based on this and other observations, a broader question arises as to whether the Ca2+ lost in diarrhea should be replaced promptly in diarrheal patients.